The Usefulness of Capsule Endoscopy for Small Bowel Tumors - Dae Young Cheung; Jin Su Kim; Ki-Nam Shim; Myung-Gyu Choi (Korean Society of Gastrointestinal Endoscopy, 2016)
Video capsule endoscopy (VCE) has expanded the range of endoscopic examination of the small bowel. The clinical application of VCE is mainly for obscure gastrointestinal bleeding (OGIB) and small bowel tumor is one of the clinically significant diagnoses of VCE, often requiring subsequent invasive interventions. Small bowel tumors are detected with a frequency of around 4% with VCE in indications of OGIB, iron deficiency anemia, unexplained abdominal pain, and others. Protruding mass with bleeding, mucosal disruption, irregular surface, discolored area, and white villi are suggested as the VCE findings of small bowel tumor. Device assisted enteroscopy (DAE), computed tomography enteroclysis/enterography and magnetic resonance enteroclysis/enterography also have clinical value in small bowel examination and tumor detection, and they can be used with VCE, sequentially or complementarily. Familial adenomatous polyposis, Peutz-Jeghers syndrome, melanoma, lymphoma, and neuroendocrine tumor with hepatic metastasis are the high risk groups for small bowel tumors, and surveillance programs for small bowel tumors are needed. VCE and radiological imaging have value in screening, and in selected cases, DAE can provide more accurate diagnosis and endoscopic treatment. This review describes the usefulness and clinical impact of VCE on small bowel tumors.